Magnetic skyrmions: advances in physics and potential applications - Fert, Albert; Reyren, Nicolas; Cros, Vincent (Nature reviews. Materials, 2017)
Magnetic skyrmions are small swirling topological defects in the magnetization texture. Their stabilization and dynamics depend strongly on their topological properties. In most cases, they are induced by chiral interactions between atomic spins in non-centrosymmetric magnetic compounds or in thin films with broken inversion symmetry. Skyrmions can be extremely small, with diameters in the nanometre range, and behave as particles that can be moved, created and annihilated, which makes them suitable for ‘abacus’-type applications in information storage and logic technologies. Until recently, skyrmions had been observed only at low temperature and, in most cases, under large applied magnetic fields. An intense research effort has led to the identification of thin-film and multilayer structures in which skyrmions are now stable at room temperature and can be manipulated by electrical currents. The development of skyrmion-based topological spintronics holds promise for applications in the mid-term furure, even though many challenges, such as the achievement of writing, processing and reading functionalities at room temperature and in all-electrical manipulation schemes, still lie ahead. Magnetic skyrmions are topologically protected spin whirls that hold promise for applications because they can be controllably moved, created and annihilated. In this Review, the underlying physics of the stabilization of skyrmions at room temperature and their prospective use for spintronic applications are discussed.